Neurological adverse events after vaccination against sars-cov-2 in the municipality of Parnaíba, Piauí - Júnior , Edmar José Fortes; Freitas, Francisco Ricardo Nascimento; Martins, Francisco Lukas Rodrigues; Barbosa, Ane Kássia de Carvalho; Abreu , Thyago Layron Sampaio de; Silva, Hildnel Rodrigues Leal; Fé, Rodrigo Campelo de Moura (Headache Medicine, 2022)
Introduction At the end of 2019, a new disease that would come to be known as COVID-19 emerged in Wuhan, Hubei province, China, caused by a virus called novel coronavirus or SARS-CoV-2. The infection has spread worldwide, causing many deaths, however, at the end of 2020, the first vaccines against this new virus appeared, approved by regulatory bodies as being effective and safe. However, since the beginning of immunization, there has been much speculation within the general population both about the supposed low efficacy and the correlation with serious post-vaccination adverse events (APVE), including deaths. Furthermore, it is highlighted in the literature that neurological manifestations are one of the main sources of AEFI. Objective: Therefore, the objective of this study is post-vaccination adverse events against covid-19 in the municipality of Parnaíba, Piauí. Objectives 1) Investigate the occurrence of post-vaccination adverse events of a neurological nature of vaccination against Sars-CoV-2 in the municipality of Parnaíba, Piauí. Methods This is a cross-sectional, observational, descriptive and epidemiological quantitative study. Data were collected from the Information Sistema de Informação de Eventos Adversos Pós-Vacinação (SI-EAPV) of Secretaria de Estado da Saúde do Piauí, in the period from January 2021 (date of the beginning of vaccination against COVID-19 in Brazil) to September 2021. The study population was concentrated in the municipality of Parnaíba, located in the state of Piauí, Brazil. According to the Instituto Brasileiro de Geografia e Estatística (IBGE), the estimated population for the municipality in question is 153,863 people. The dependent variable is the presence of neurological manifestation as an outcome: yes/no. The other variables analyzed were color/race, sex and the description of the vaccine used. (Too see the complete abstract, please, check out the PDF).